PENERAPAN MANAJEMEN HIPERTERMI TERHADAP TERMOREGULASI PADA ANAK DENGAN KEJANG DEMAM DI IGD RSUD LABUANG BAJI - Nurpaisa; Sudarman; Suci Hardianti Suharto Putri (CV. Adiba Aisha Amira, 2026)
Febrile seizures are a common neurological condition in children aged 6 months–5 years, characterized by an increase in body temperature ≥38°C without central nervous system infection. Hyperthermia management through warm compresses is an effective non-pharmacological intervention to help improve thermoregulation. This study aimed to apply hyperthermia management to improve thermoregulation in children with febrile seizures in the emergency room (ED) of Rsud Labuang Baji. The results showed that after 30 minutes of intervention, body temperature decreased from 39.9°C to 36.9°C, and there were no recurrent seizures during observation. In conclusion, simple interventions such as warm compresses can be an important part of initial management in the ED to prevent complications.